Combustion characteristics of methane-diesel dual-fuel engines at light load conditions with different injection strategies - Hegab, Abdelrahman H.I. (2018)
An experimental investigation has been carried out to examine the combustion process in methane-diesel dual-fuel engines under light load conditions, with different ratios of the two fuels and different injection strategies of the diesel pilot. The study has used a 2.2L turbocharged common rail compression ignition (CI) engine, converted for dual-fuel (DF) operation while retaining the ability to run on diesel fuel only. The main area of interest has been the change of heat release characteristics with methane substitution for diesel fuel, and what gives rise to these changes. The focus has been put on the light load operating conditions, where the engine suffers poor fuel economy and increased instability owing to the very weak mixture strength of the gaseous fuel and air. An effort has been made to identify the minimum size of the diesel pilot required for the ignition of the very lean methane-air mixture at near-idle low-load operating conditions.